Pituitary Stalk Thickening - Arregger, Alejandro Luis (2018)
MRI revealed enlargement of the pituitary stalk in two patients with different clinical presentations. A 60 y/o female had autoimmune hypothyroidism associated with blunted cortisol response to ACTH, while the other, a 30 y/o female had amenorrhea and polyuria with high plasma and low urinary osmolality.